การเสริมสร้างประสิทธิภาพในการปฏิบัติงานของพนักงานบริษัท โบ๊ทบุ๊คส์ออฟฟิศเซ็นเตอร์ จำกัด - เวียงแก้ว, เวรัญศิยา (Journal of Graduate School Sakon Nakhon Rajabhat University, 2018)
The purpose of this study was to determine work performance development and motivation of personnel at Boat Book Office Center Co., Ltd. The samplings were 95 personnel of Boat Book Office Center Co., Ltd. By using questionnaire as a tool for data collection and statistics application was percentage, mean, standard deviation, t-test, one-way Anova, and regression. Data from the study revealed that most of respondents were females, age over 31 years old, single marital status, earned bachelor degree, average income between 15,000-20,000 baht, and work for the company over 3 years. Factors of work performance and motivation were in the high level. The test of hypothesis found that the personal different such as gender, age, marital status, level of education, and income affected work performance development and motivation of personnel at Boat Book Office Center Co., Ltd. at significant level 0.05. The different of personal hygiene affected the work performance of personnel at Boat Book Office Center Co., Ltd. at statistical significant at 0.05 level. Recommendations from the study were that superiors should appreciate work done by personnel, encourage freedom of work performance and decision making under their responsibilities, analyze and provide variety of job responsibility, support career advancement, inform company news and update regularly, adjust income to cost of standard living, and provide enough appropriate equipment in order to get better work performance.